PENGELOLAAN (MANAGING) PROSES DAN SUMBER DAYA TEKNOLOGI YANG TEPAT PADA PEMBELAJARAN FIQH DI MADRASAH ALIYAH NEGERI 1 MERANGIN KELAS XII - Dikin, Musol; Sari, Repa Topia; Musfirah, Musfirah; Mainnah, Khairattul Mut; Nuzli, Muhammad; Mariya, Yuni (Institut Agama Islam Syekh Maulana Qori Bangko, 2024)
Management (Managing) Processes and Technological Resources appropriately Fiqh Learning Materials at Madrasah Aliyah Negeri 1 Merangin Class XII, the management carried out by the teachers there is quite good. However, the process of using technology at MAN 1 Merangin is still lacking. The research findings that we have carried out are that the process of using technology for Fiqh material at MAN 1 Merangin Class Then the management of technological resources has been managed well by the school because the principal facilitates technology so that teachers can use it in learning after training in the use of technology. In the research that the author conducted, the author used a descriptive method consisting of observation, interviews and documentation related to what happened in the field. The author’s research results found that appropriate management of technological processes and resources in Fiqh learning materials at Madrasah Aliyah Negeri 1 Merangin Class XII has been carried out quite well so that students can study peacefully and comfortably.